Physical Stability of Sea Buckthorn Oil Nanoemulsion with Tween 80 Variations - Ayu Shabrina; Icha Sabrina Milenia Khansa (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Sea buckthorn oil (SBO) contains fatty acids that have an anti-aging effect. The delivery system ofSBO can be improved by a nanoemulsion system. The purpose of this study was to determine thephysical stability of SBO nanoemulsion (NSB) with Tween 80 variation. NSB was made with 1% SBOand Tween 80 variation of 35% (FI); 40% (FII) and 45% (FIII). NSB was stored in a climatic chamberat 30 ± 2°C and RH of 65%±5% for 90 days. Samples were taken before storage on the 15th, 30th,60th, and 90th days. Evaluations were carried out including appearance, particle size, polydispersityindex (PI), transmittance percentage (TP), pH, and viscosity. Quantitative data were analyzed withmultivariate analysis. The result showed that NSB formulas were yellowish-orange and clear. Thedroplet size in FII and FIII was stable (p > 0.05) with a range of 12-15 nm with PI < 0,5. All formulashad TP > 95% with a pH of 7.50–7.6. The viscosity of all formulas was 1.2-1.9 dPa.s and characterizedas Newtonian. Increasing the concentration of tween 80 can reduce droplet size and PI. Tween 80 at aconcentration of 35-45% produces sea buckthorn nanoemulsion which is stable for 90 days of storage.